2014
DOI: 10.3945/ajcn.114.086900
|View full text |Cite
|
Sign up to set email alerts
|

Skin and plasma carotenoid response to a provided intervention diet high in vegetables and fruit: uptake and depletion kinetics , , ,

Abstract: Background: Objective biomarkers are needed to assess adherence to vegetable and fruit intervention trials. Blood carotenoids are considered the best biomarker of vegetable and fruit intake, but collecting blood is invasive and the analyses are relatively expensive for population studies. Resonance Raman spectroscopy (RRS) is an innovative method for assessing carotenoids in skin noninvasively. Objective: Our objective was to compare blood carotenoid concentrations with skin carotenoid assessments by RRS durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 30 publications
(42 reference statements)
6
84
1
1
Order By: Relevance
“…34 Resonance Raman spectroscopy has been used extensively in several nutritional epidemiology studies and is considered an excellent noninvasive biomarker of fruit and vegetable intake and has been validated by skin biopsy studies to correspond well with skin carotenoid content measured by HPLC 13 and serum carotenoid levels (Table 3). 13,18,19,27,3540 After daily calibration, a 488-nm blue laser light illuminates a small patch of the subject's palm for approximately 30 seconds. Back-scattered light is collected, and a holographic notch filter rejects Rayleigh-scattered light.…”
Section: Methodsmentioning
confidence: 99%
“…34 Resonance Raman spectroscopy has been used extensively in several nutritional epidemiology studies and is considered an excellent noninvasive biomarker of fruit and vegetable intake and has been validated by skin biopsy studies to correspond well with skin carotenoid content measured by HPLC 13 and serum carotenoid levels (Table 3). 13,18,19,27,3540 After daily calibration, a 488-nm blue laser light illuminates a small patch of the subject's palm for approximately 30 seconds. Back-scattered light is collected, and a holographic notch filter rejects Rayleigh-scattered light.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the validation of the RRS methodology for skin carotenoid measurements was a recent study that showed high RRS/HPLC plasma correlations for subjects participating in controlled dietary intervention phases [10]. The study was approved by the Institutional Review Board of the University of North Dakota.…”
Section: Skin Carotenoid Screening In Dietary Intervention Studiesmentioning
confidence: 99%
“…Plasma carotenoids and TBSs are increased in response to consumption of highcarotenoid diets (5,12,14). Skin and serum carotenoids reflected both a low-carotenoid regimen followed by a high-carotenoid regimen (20).…”
Section: Introductionmentioning
confidence: 99%